1987
DOI: 10.1161/01.str.18.5.882
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral flow reduction in unilateral stroke: evidence for transhemispheric diaschisis.

Abstract: Using clinical presentation, angiography, computed tomography, and nuclear magnetic resonance imaging, 7 patients were identified who had strictly unilateral hemispheric infarction and unilateral cerebrovascular disease. In 6, cerebral blood flow measured by fluorine-18-fluoromethane inhalation and positron emission tomography was reduced in the contralateral hemisphere (p<0.05). Multiple regression analysis demonstrated a high correlation between contralateral flow reduction and the degree of flow impairment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 17 publications
2
25
0
1
Order By: Relevance
“…These reductions were small and were not accompanied by decreases in right SEP amplitudes. Contralateral reduction of CBF has been described experimentally 18 and clinically 19 and has been attributed to transcallosal diaschisis. 19 - 20 However, contralateral CBF reductions in the other three groups were minor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These reductions were small and were not accompanied by decreases in right SEP amplitudes. Contralateral reduction of CBF has been described experimentally 18 and clinically 19 and has been attributed to transcallosal diaschisis. 19 - 20 However, contralateral CBF reductions in the other three groups were minor.…”
Section: Resultsmentioning
confidence: 99%
“…Contralateral reduction of CBF has been described experimentally 18 and clinically 19 and has been attributed to transcallosal diaschisis. 19 - 20 However, contralateral CBF reductions in the other three groups were minor. Thus, contralateral CBF reduction in group MCABCCAO-120 can be largely attributed to the bilateral CCA occlusion.…”
Section: Resultsmentioning
confidence: 99%
“…ischemia [6, 7, 8, 9, 10, 11, 21, 22]. Diaschisis has been predominantly observed in 3 types of ischemic strokes: (a) in the cerebellum contralateral to a supratentorial lesion [10, 21, 23, 24]; (b) in the unaffected hemisphere as a result of a cortical lesion [6, 7, 8, 9, 10, 11, 12], and (c) in the cortex after a deep …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, excluding a few case reports of crossed cerebellar diaschisis [21, 23, 27], no studies have been performed in humans in the initial hours after ischemic events. In the current study, the occurrence of transhemispheric diaschisis, already observed in the subacute and chronic stages [6, 7, 8, 9, 10, 11, 12, 22], was evaluated for the first time within the first few hours from the ischemic stroke. There is only one other clinical study that has estimated the occurrence of diaschisis in the unaffected hemisphere (through an analysis of its metabolism) in the acute stage (within 18 h, mean 11 h).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation